2023
DOI: 10.1177/03331024231160743
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, clinical characteristics and associated factors of cardiac cephalalgia: A prospective study

Abstract: Background The prevalence of cardiac cephalalgia is unknown and there is limited information about its clinical features. We aimed to assess the prevalence of cardiac cephalalgia, its clinical characteristics and associated factors. Methods We conducted a prospective study of patients with suspected acute coronary syndrome admitted to the Cardiology Service at Hospital Clínico Universitario Lozano Blesa, Zaragoza, Spain, over a one-year period. We interviewed patients within the first 24 hours of admission usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In relation to criterion C3, studies have shown that headache characteristics in patients with cardiac cephalalgia are very variable (46) and the compliance rate of some of the sub-criteria, especially C3b and C3d, is low. For this reason and to simplify the diagnostic criteria, we suggest that criterion C3 should be removed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In relation to criterion C3, studies have shown that headache characteristics in patients with cardiac cephalalgia are very variable (46) and the compliance rate of some of the sub-criteria, especially C3b and C3d, is low. For this reason and to simplify the diagnostic criteria, we suggest that criterion C3 should be removed.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a series of cases study of 54 patients with cardiac cephalalgia identified in a prospective study of consecutive patients admitted to the Cardiology Service at Hospital Cl ınico Universitario Lozano Blesa in Zaragoza, Spain, with suspected acute coronary syndrome (ACS) from January 2021 and January 2022 (6). A complete description of material and methods has been given elsewhere (6).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations